2009
DOI: 10.1007/s11552-008-9160-9
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Evaluation of Dupuytren's Disease Incidence and Prevalence Rates in Relation to Etiology

Abstract: Dupuytren's Disease (DD) is a common, fibroproliferative disorder affecting the palmar surface of the hands which is often irreversible and progressive. Understanding the epidemiology of DD is important in order to provide clues to its etiopathogenesis. This review aims to evaluate the epidemiological studies carried out in DD since 1951. Studies evaluating the epidemiology of DD were searched using Medline, Pubmed, and Scopus which dated back from 1951 to current date. Inclusion criteria were any studies inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
141
1
14

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(159 citation statements)
references
References 91 publications
(108 reference statements)
3
141
1
14
Order By: Relevance
“…23 Africa and the rest of Asia had only sporadic cases in this report. In a Japanese study, Egawa et al 21 suggested that the incidence of Dupuytren's disease in Japan differs little from that in northern Europe.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…23 Africa and the rest of Asia had only sporadic cases in this report. In a Japanese study, Egawa et al 21 suggested that the incidence of Dupuytren's disease in Japan differs little from that in northern Europe.…”
Section: Discussioncontrasting
confidence: 45%
“…Hindocha et al 23 described the prevalence of Dupuytren's disease in northern Europe as between 18 and 39%, North America 4 to 26%, Oceania 23% and Japan 19% in an epidemiology evaluation of the disease in 49 papers from across the globe. 23 Africa and the rest of Asia had only sporadic cases in this report.…”
Section: Discussionmentioning
confidence: 99%
“…5 Hindocha et al report a mean age of onset in familial DD of 49 years and 55 in non-familial DD. 13 This may explain the very low percentage of coexisting DD in the study by Levine et al 21 Finally, the varying or unknown follow-up periods in the different studies may explain the wide ranges of coexisting DD in PD.…”
Section: Discussionmentioning
confidence: 93%
“…Population structure, the prevalence of associated diseases and the diagnostic criteria of DD, makes the understanding of epidemiology quite difficult. 13 The literature concerning coexisting DD in patients presenting with PD shows wide ranges varying from 0.01 to 58.8%. 5,9,[14][15][16][17][18][19][20][21][22][23][24] The aim of this study is to investigate the coexistence of DD in a consecutive series of patients with PD and their clinical characteristics, presenting at the outpatient urological clinic of the University Medical Centre Groningen, The Netherlands.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to impairments in hand function and problems with performance of daily activities as well as quality of life [2][3][4][5]. The prevalence of DD increases with age and varies depending on sex [6,7] and ethnic group [7]. In Western populations, a mean prevalence of 21% has been reported among men and 5% among women aged 65 [6].…”
Section: Introductionmentioning
confidence: 99%